Large-scale curvature sensing by directional actin flow drives cellular migration mode switching - Chen, Tianchi; Callan-Jones, Andrew; Fedorov, Eduard; Ravasio, Andrea; Brugués, Agustí; Ong, Hui Ting; Toyama, Yusuke; Low, Boon Chuan; Trepat, Xavier; Shemesh, Tom; Voituriez, Raphaël; Ladoux, Benoît (Nature Physics, 2019)
Cell migration over heterogeneous substrates during wound healing or morphogenetic processes leads to shape changes driven by different organizations of the actin cytoskeleton and by functional changes including lamellipodial protrusions and contractile actin cables. Cells distinguish between cell-sized positive and negative curvatures in their physical environment by forming protrusions at positive curvatures and actin cables at negative curvatures; however, the cellular mechanisms remain unclear. Here, we report that concave edges promote polarized actin structures with actin flow directed towards the cell edge, in contrast to well-documented retrograde flow at convex edges. Anterograde flow and contractility induce a tension anisotropy gradient. A polarized actin network is formed, accompanied by a local polymerization–depolymerization gradient, together with leading-edge contractile actin cables in the front. These cables extend onto non-adherent regions while still maintaining contact with the substrate through focal adhesions. The contraction and dynamic reorganization of this actin structure allows forward movements enabling cell migration over non-adherent regions on the substrate. These versatile functional structures may help cells sense and navigate their environment by adapting to external geometric and mechanical cues.
CRIS-Team Scopus Importer:2024-02-19